Increasing the reliability of bioenergy parks utilizing agricultural waste feedstock under demand uncertainty - Benjamin, Michael Francis D. (Animo Repository, 2020)
Bioenergy parks are multi-product industrial complexes that convert residual biomass from agro-food systems into valuable products such as biofuel and power. By utilizing waste from food production, such systems can mitigate competition for resources at the food-water-energy nexus. A bioenergy park consists of individual plants that are integrated with each other to improve material and energy efficiency and attain more sustainable operations. However, such advantages can be negated by vulnerability of integrated systems to cascading failures triggered by equipment failure or feedstock supply perturbations. Seasonal variations in the demand may also cause reductions in throughput compared to normal production levels, resulting in similar cascading disruptions. The reliability of bioenergy parks can be enhanced by having redundancy measures. However, as this approach is subject to budget constraints, it is important to identify the most critical plant in the bioenergy park. This key step economizes redundancy allocation and avoids overdesigning system capacities. This work applied this integrated framework to address criticality of process units or plants in bioenergy parks, considering demand uncertainties. The method increases overall reliability of bioenergy parks by allocating standby inventory or supply. Two bioenergy parks are analyzed as case studies to demonstrate the integrated method. © 2020 Elsevier Ltd